2017
DOI: 10.3389/fpsyg.2016.02028
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Representational Interactions: Interface and Overlap Mechanisms

Abstract: A crucial question facing cognitive science concerns the nature of conceptual representations as well as the constraints on the interactions between them. One specific question we address in this paper is what makes cross-representational interplay possible? We offer two distinct theoretical scenarios: according to the first scenario, co-activated knowledge representations interact with the help of an interface established between them via congruent activation in a mediating third-party general cognitive mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Whichever is the underlying cause, these modulations pose challenges for accounts of situated sentence comprehension ( Knoeferle and Crocker, 2006 , 2007 ; Altmann and Kamide, 2007 ; but see Guerra and Knoeferle, 2014 , 2017 ) as they endeavor to accommodate the effects of visually-derived representations of objects (e.g., cards in Guerra and Knoeferle, 2014 , 2017 ). They also enrich the discussion about the extent (and limits) of sensorimotor interaction with language processing (e.g., Zwaan, 2014 ; Mahon, 2015 ; Myachykov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 82%
“…Whichever is the underlying cause, these modulations pose challenges for accounts of situated sentence comprehension ( Knoeferle and Crocker, 2006 , 2007 ; Altmann and Kamide, 2007 ; but see Guerra and Knoeferle, 2014 , 2017 ) as they endeavor to accommodate the effects of visually-derived representations of objects (e.g., cards in Guerra and Knoeferle, 2014 , 2017 ). They also enrich the discussion about the extent (and limits) of sensorimotor interaction with language processing (e.g., Zwaan, 2014 ; Mahon, 2015 ; Myachykov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 82%
“…If the underlying magnitude component is indeed shared between different representations, then we may expect cross‐domain priming effects between word length and other representational features. Some recent reports confirm that two seemingly different representations indeed exhibit cross‐domain priming effects (Lachmair, Dudschig, de la Vega, & Kaup, ; Myachykov et al ., ; Scheepers et al ., ; de la Vega, De Filippis, Lachmair, Dudschig, & Kaup, 2012). Neither of these reports, however, (1) use a free production task nor (2) address the surface‐form features similar to the syllabic length examined here.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, participants’ left‐hand responses were faster when they judged parity of smaller numbers (e.g., 1 or 2) while right‐hand responses were faster for larger numbers (e.g., 8 or 9), suggesting that accessed number representations are arranged along a Mental Number Line (MNL) with numerical magnitude monotonically increasing from left to right. Numerous studies that followed demonstrated an intimate link between SNARC and visual attention, by showing that SNARC‐related processing differences result from attentional displacement (Fischer, Castel, Dodd, & Pratt, ; Fischer, Warlop, Hill, & Fias, ; Myachykov, Chapman, & Fischer, ) and by documenting neuroanatomical links between oculomotor control and mental arithmetic (Knops, Thirion, Hubbard, Michel, & Dehaene, ). Furthermore, SNARC was validated in studies that employed numerous tasks, with different effectors, including hand, foot, eye, and head movements, and in different modalities, suggesting that it reflects a relatively universal, task‐independent, and supra‐modal representation of numerical magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kruley et al (1994) suggest that spatial representations are used to represent non-spatial information. Negative and positive emotions, for example, can be mapped in contrasting areas of space (Myachykov et al, 2017). Internal scene construction, then, suggests how early processing can be related to higher level of interpretation over shorter or longer time scales, through support for actual and potential causal relations at different levels of abstraction.…”
Section: Future Directions: Internal Scene Construction and The Episomentioning
confidence: 99%